WEBSITE BASED INFORMATION SYSTEM DEVELOPMENT TO IMPROVE LEARNING ACHIEVEMENTS - Al Abiyyu Mahdy; Alexon Alexon (UNIB Press, 2019)
The development of an information system package for computer and network- based network engineering expertise aims to improve learning achievement in computer and basic network subjects at SMK IT Rabbi Radhiyya. The type of research carried out is Research and Development (R&D), this development adapts to the needs of the field. The research subjects were class x computer and network engineering expertise packages at SMK IT Rabbi Radhiyya Rejang Lebong, Data collection methods namely: coordination, interviews, questionnaires and test exams. The data analysis technique of learning achievement uses one group t test and between groups. Information on developing a web-based information system on computer and network engineering expertise packages on basic computer and network lessons can improve learning achievement